Feasibility of Corn Silk Eco-Enzyme as Essence in Sheet Mask with Antioxidant Content - Nisa, Zakiya Ayu; Agustin, Eny Widhia; Kusumastuti, Adhi; Achmadi, Taofan Ali (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
Air pollution level in Indonesia can cause oxidative stress which can impact the antioxidant defenses of the skin so it can trigger premature aging problems. Skin protection should focus on the application of topical antioxidants which include flavonoids as antioxidants. Furthermore, corn silk containing flavonoids has the potential to be used as a topical preparation in the form of a sheet mask as an antioxidant in preventing premature aging. Corn silk which is processed using the fermentation method becomes an eco-enzyme since it can act as a good catalyst and produce antioxidants. The aim of this research is to analyze the feasibility of eco-enzyme as an essence in sheet mask preparations with antioxidant content which meets the preparation evaluation requirements. The method used in this research consisted of making corn silk eco-enzyme which was homogenized with other chemicals to become an essence sheet mask and packaged by using paper sheets in foil bags. The research results show that preparations with eco-enzyme concentrations in each formula, namely 10% (F1), 20% (F2), and 30% (F3), have good physical evaluations and met test standards which included organoleptic, pH, homogeneity, spreadability, adhesion, and stability tests. Moreover, the antioxidant activity test shows the IC50 values for each formula are 190.67 µg/mL, 185 µg/mL, and 96.75 µg/mL, respectively. The conclusion is that the F3 with a concentration of 30%, shows the best antioxidant activity, having an IC50 value of 96.75 µg/mL, which is classified as strong. In addition, the results of this research prove that the eco-enzyme from corn silk is suitable for use in preparing essence sheet masks with antioxidant content.